2016
DOI: 10.1111/febs.13793
|View full text |Cite
|
Sign up to set email alerts
|

Understanding single‐pass transmembrane receptor signaling from a structural viewpoint—what are we missing?

Abstract: Single‐pass transmembrane receptors are involved in essential processes of both physiological and pathological nature and represent more than 1300 proteins in the human genome. Despite the high biological relevance of these receptors, the mechanisms of the signal transductions they facilitate are incompletely understood. One major obstacle is the lack of structures of the transmembrane domains that connect the extracellular ligand‐binding domains to the intracellular signaling platforms. Over a period of almos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 147 publications
(395 reference statements)
0
43
1
Order By: Relevance
“…Consequently, only the four remaining relative motions can occur: Moving toward or away from each other (which amounts to association or dissociation); moving perpendicular to the membrane plane (piston‐like motions); pivoting (also called scissoring or tilting); and finally rotation (gearbox‐like) . We note that the question of TM signaling by single pass proteins is widely discussed in the context of eukaryotic proteins, such as receptor tyrosine kinases …”
Section: Transmembrane Signaling: What Are the Possible Mechanisms?mentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, only the four remaining relative motions can occur: Moving toward or away from each other (which amounts to association or dissociation); moving perpendicular to the membrane plane (piston‐like motions); pivoting (also called scissoring or tilting); and finally rotation (gearbox‐like) . We note that the question of TM signaling by single pass proteins is widely discussed in the context of eukaryotic proteins, such as receptor tyrosine kinases …”
Section: Transmembrane Signaling: What Are the Possible Mechanisms?mentioning
confidence: 99%
“…[77,78] We note that the question of TM signaling by single pass proteins is widely discussed in the context of eukaryotic proteins, such as receptor tyrosine kinases. [79][80][81][82] In dimeric double-pass receptors, presence of additional transmembrane helices further restricts the motions available to individual helices. At the same time, because the number of the helices is increased, the number of the collective motions is also increased.…”
Section: Transmembrane Signaling: What Are the Possible Mechanisms?mentioning
confidence: 99%
“…Therefore, the liquid order of a particular membrane microdomain might have an impact on the orientation behavior of membrane proteins, as shown here [50]. It has been reported that the NMR structure of an isolated TLR3-TM domain in dodecylphosphocholine micelles exists as a right-handed dimer with a helix-crossing angle of -51.1 • [51]. The substantial tilt and curvature and the consistent crossing angle of TM helices in our simulations indicate that the hydrophobic mismatch shapes the TM domain organization of full-length TLR3 in the cell membrane [52].…”
Section: Discussionmentioning
confidence: 78%
“…Currently, there is very little information regarding MRAP2 structure and it is not uncommon for single-pass transmembrane proteins to have intrinsically disordered domains making them difficult to study using classic biophysical techniques 30 . These disordered regions often have functional importance since this flexibility allows them to interact with multiple protein partners.…”
Section: Discussionmentioning
confidence: 99%